Awareness of dengue and practice of dengue control measures among urban population in Tamil Nadu, India - Kumar T., Varun; Pandian M., Vijay; P., Swaminathan; Kumar T., Ravi (International Journal Of Community Medicine And Public Health, 2018)
Background: The dengue infection has become endemic in India as a result of changing environmental conditions and lack of awareness among the public. So, the present study was conducted with the objectives of studying the awareness of dengue and dengue control practices among urban population in Coimbatore, Tamil Nadu. Methods: The study was of cross sectional design conducted in the fever clinic of Government Medical College and ESI Hospital, Coimbatore, Tamil Nadu. Systemic random sampling was done to select the study participants. A pre-tested, pre-validated semi-structured questionnaire was used to obtain data was obtained from 270 individuals during August to November 2017. Results: Among the study participants, 254 (94.1%) had heard of dengue. Among them, 145 (53.7%) correctly identified the symptoms of dengue, 221 (81.6%) correctly responded that the dengue is transmitted by Aedes mosquitoes and 82 (30.4%) had correct knowledge about Aedes mosquito breeding places. Younger age group individuals and those with higher education had significantly better awareness about mosquito control measures (p<0.005). Conclusions: Majority of the study population was aware about dengue, only half of them knew about the symptoms of dengue and only one-third correctly knew about breeding habitats of Aedes mosquitoes. Therefore, already functioning health campaigns should ensure that the knowledge acquired is put into practice.